2008
DOI: 10.1002/joc.1657
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to precipitation series completion in climatological datasets: application to Andalusia

Abstract: ABSTRACT:Complete monthly series of precipitation data have been generated for 932 stations run by the Instituto Nacional de Meteorología (INM) in Andalusia (Andalucía, southern region of Spain) and some adjacent areas for the period 1961-2000 using a new method for the estimation of missing data. The proposed method fills in the gaps in the climatological series for a target station using precipitation data from neighbouring stations with a similar precipitation pattern. Particular emphasis is made in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 17 publications
0
40
0
3
Order By: Relevance
“…Hutchinson (1995) used thin-splines for interpolation of precipitation data. Ramos-Calzado et al (2008) proposed a new approach for estimating missing precipitation data considering the rainfall measurement uncertainty. Improvements were achieved in the estimation of precipitation data when the stations with lowest measurement uncertainty were selected in the interpolation process.…”
Section: Introductionmentioning
confidence: 99%
“…Hutchinson (1995) used thin-splines for interpolation of precipitation data. Ramos-Calzado et al (2008) proposed a new approach for estimating missing precipitation data considering the rainfall measurement uncertainty. Improvements were achieved in the estimation of precipitation data when the stations with lowest measurement uncertainty were selected in the interpolation process.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of these methods for the interpolation of precipitation data has been investigated by a number of comparative studies, both on a monthly and daily basis (e.g. Ashraf et al, 1997;Teegavarapu and Chandramouli, 2005;Ramos et al, 2008), and generally found to be greater than that of weighting approaches. In particular, Eischeid et al (2000) demonstrated that multi-linear regression (MLR) outperforms most of the commonly used techniques concerning missing data handling in daily resolution precipitation series.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a great deal of other research has been carried on sub-regional and local scales (e.g. Romero et al 1998, Ceballos et al 2004, Saladié et al 2004, del Río et al 2005, Caramelo & Manso-Orgaz 2007, Ramos-Calzado et al 2008, which results are difficult to compare as station densities and the period under examination vary greatly (see the recent review by Gonzalez-Hidalgo et al 2010).…”
Section: Introductionmentioning
confidence: 99%